Correlation cyclooxygenase-2 expression and histopathological grading in locally advanced breast cancer - Maulidan, Yasser; Syamsu, Salman A.; Thabry, Rudy; Abidin, Zainal (International Journal of Research in Medical Sciences, 2019)
Background: Cyclooxygenase-2 (COX-2) is involved in the carcinogenesis process and tumor progression into cancer. It has been reported recently, there was a COX-2 expression at breast cancer. Patients with a high level of COX-2 expression can have a local recurrence and decrease life expectancy, and an increase of COX-2 expression in tissue likelihood has prognostic value. This study aims to correlation cyclooxygenase-2 (cox-2) expression and histopathological grading in locally advanced breast cancer patient in AW Sjahranie Hospital in Samarinda city. Methods: This study was an observational study with crossectional design to analysis the correlation COX-2 expression and histopathological grading in patients with locally advanced breast cancer and using data analysis with the Chi-Square test. Results: The results showed that the correlation was not significant (P>0.05), where there was no correlation of COX-2 expression with histopathological grading (P=0.221) and there was no correlation with the last condition of patients (P=0.61). Although patients with breast cancer high grade and moderate grade percentages were significantly higher in positive COX-2 than in COX-2 negative expression. Conclusions: There were no correlation between COX-2 expression and histopathological grading and there was no significant relationship between COX-2 expression and the last condition, as evidenced by the statistical test results showing that the differences were not significant.